Development of Student Worksheet with Problem Based Learning Oriented to Train Students Creative Thinking Skill in Acid Base Matter by Using Natural Products (UNESA Journal of Chemical Education, 2020)
A research had been conducted on developing Student Worksheet oriented to Problem Based Learning (PBL) for training students’ creative thinking skill in acid-base material. This study aims to determine the validity, practicality, and effectiveness of the developed Student Worksheet. The procedure of development research uses the steps of product development by Thiagarajan, it is the 4-D (four-D) model which is limited to the development stage only. The feasibility of Student Worksheet in validity aspect is obtained from the results of the validation assessment by three validators consisting of two chemistry lecturers and one chemistry teacher. The results of the validation assessment by validators are 88.33% on the criteria of content validity and 82.81% on the criteria of construct validity with a very valid category. The feasibility of effectiveness is reviewed from the post test results of students creative thinking skills and it is obtained that the Class Achievement Index is 94,12% with a very high category, also for each component as fluency got 100%, flexibility got 100%, elaboration got 91,50%, and originality got 100% with very high category for all . The feasibility of practical is based on the responses from students which had received much positive responses as 91.31% with very practical categories and also the observation result of students relevant activities during learning using Student Worksheet with the percentage of first day got 98,89% and second day got 97,78% with both in very high interpretation. Keywords: Student Worksheet, Problem Based Learning, creative thinking, acid-base